Martin Young's dory, with the house in the background - Dollard, Calwyn (1980)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Boatbuilding as a Craft ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Boatbuilding as a Craft." Photos P9545-P9553 liées au document TS-80-337 -- Photos linked to document TS-80-337